TISSUE ENGINEERING OF THE ATRIOVENTRICULAR VALVE: DECELLULARIZED MATRIX IN OVINE MITRAL ALLOGRAFT MODEL - P. P. Iablonskii; S. Cebotari; I. Tudorache; A. Hilfiker; S. M. Yashin; A. Haverich (Вестник трансплантологии и искусственных органов)
Aim. Development of the tissue engineered matrix for the atrioventricular valve graft in a large animal model. Materials and мethods. The study was performed on ovine mitral valves (n = 100). The decellularization of the whole mitral valve grafts was performed using 21 different detergent-based protocols. The effectiveness of the decellularization was investigated by immunofluorescent staining for DNA (as a marker of intracellular antigens) and α-GAL (as a marker of membrane-associated antigens), as well as DNA quantification. The mechanical properties and the repopulation potential were analyzed. The structure and repopulation rate analysis included hematoxylin-eosin, Movat’s pentachrome and Van Gieson histological staining, and immunofluorescent staining for collagen I and IV, as well as endothelial cell markers. Results. The protocols that included the gradual rise of the detergent solution were shown to be the most effective for the decellularization of the whole mitral valve graft. At the same time, the detergents alone failed to remove α-GAL. The reducing agent enhanced the decellularization, which resulted in complete removal of DNA and α-GAL, according to immunofluorescent staining. DNA quantification showed a 96.4% reduction in DNA content. The mechanical properties were shown to be comparable to the native tissue. The reseeding of the decellularized tissue showed a potential for the repopulation. Conclusions. A new matrix for the atrioventricular valve substitute could be developed using the decellularization as the initial step of the valve tissue engineering. The detergent combined with a reducing agent showed significantly better results compared to the detergents alone for the mitral valve decellulrization. The matrix demonstrated mechanical properties, comparable with the native one, and the potential for the repopulation.